An Analysis Of Figurative Language Found in Casting Crowns Healer’s Album - Butar Butar, Fina Sondang Angelina; Pasaribu, Yessy Octaviana; Sidabutar, Usman (CV. Utility Project Solution, 2023)
This study aims to identify the types of figurative language used in the album Healer by Casting Crowns and the dominant types of figurative language found in the album. The method used in this research is the descriptive-qualitative method. This research uses Harun's theory (2019). The researcher found seven types of figurative language used in the album Healer by Casting Crowns, such as hyperbole, irony, metaphor, personification, simile, litotes, metonymy and Synecdoche. This study aims data was collected by reading the lyrics of the album song Healer by Casting Crowns. On the album Healer by Casting Crowns, there is hyperbole (7 data points), personification (1 data ), and irony (1 data ), Sarcasm (0), Synecdoche (3 data), Satire (1 data), Metaphor (0 data), Metonymy (18 data), Simile (0 data), and Litotes (1 data). This study found that the most dominant types of figurative language were metonymy with a percentage of 56.25%, followed by hyperbole with a percentage of 21.85%, personification (3.13%), irony (3.13%), sarcasm (0%), synecdoche (9.38%), satire (3.13%), metaphor (0%), metonymy (56.25%), simile (0%), and litotes (3.13%). Of these percentages, researchers can conclude that the most dominant data is metonymy (56.25%), and the smallest are three types of figurative language, namely sarcasm (0%), metaphor (0%), and simile (0%). Keywords: Figurative Language, Album, Spiritual Song, Lyrics